OIL AND GAS IN THE ADRIATIC FORELAND, ITALY. (July 2015) - Cazzini, F.; Zotto, O. Dal; Fantoni, R.; Ghielmi, M.; Ronchi, P.; Scotti, P.
<x xml:space="preserve">Abstract</x> The offshore Adriatic Basin holds more than 50% of Italian gas reserves together with significant volumes of oil. A number of large and giant‐size biogenic gasfields and medium to large oilfields have been discovered here during the past 60 years. Two petroleum systems have been identified: a Plio‐Pleistocene biogenic gas system, and an Upper Triassic – Lower Jurassic oil system. These systems are described in this paper within a regional geological framework, with particular focus on petroleum system elements (source, reservoir, seal, trap and charge). The biogenic gas play was for several decades the prime focus of Italian E&P efforts throughout the Adriatic area but is now mature, and significant additional discoveries are unlikely to be made without a breakthrough in DHI (direct hydrocarbon indicator) technology. The Mesozoic oil play is as yet unproved in the northern Adriatic area, where large anticlinal structures at depths of up to ca. 6000 m are available for exploration and constitute high‐risk – high‐reward targets. By contrast, the play is proved in the Central and Southern Adriatic where several oilfields are currently producing. Exploration targets still exist here and may generate medium‐sized discoveries although the prevalent heavy‐oil phase may jeopardize their economic value.